2009
DOI: 10.1111/j.1538-7836.2009.03538.x
|View full text |Cite
|
Sign up to set email alerts
|

The molecular mechanisms of immunomodulation and tolerance induction to factor VIII

Abstract: Summary. Successful factor (F) VIII replacement therapy in hemophilia A patients is confounded by the generation of inhibitory anti-FVIII antibodies (Ab) in 25-30% of treated patients. These antibodies, termed ÔinhibitorsÕ, significantly increase morbidity within the hemophilia population and lower the quality of life for these patients. For the past 30 years, immune tolerance induction (ITI) has been the standard therapy to elicit immunological tolerance to FVIII in the clinic. ITI works well in approximately… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
72
0
2

Year Published

2010
2010
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(78 citation statements)
references
References 76 publications
4
72
0
2
Order By: Relevance
“…42,43 The exact mechanism of the immune-tolerance induction in this hemophilia A dog study is currently unknown. Previous work in murine and nonhuman primate models has shown that sustained AAV-mediated expression of transgenes can induce tolerance, and that this sustained expression is dependent on regulatory T cells.…”
Section: Discussionmentioning
confidence: 97%
“…42,43 The exact mechanism of the immune-tolerance induction in this hemophilia A dog study is currently unknown. Previous work in murine and nonhuman primate models has shown that sustained AAV-mediated expression of transgenes can induce tolerance, and that this sustained expression is dependent on regulatory T cells.…”
Section: Discussionmentioning
confidence: 97%
“…These new approaches have been tested in haemophilia A models and involve B cell and T cell immune modulation or FVIII antigen presentation (recently reviewed in Waters & Lillicrap, 2009). Although there would be many challenges to overcome in translating to the clinic, the development of tolerance induction strategies based on immune modulation appears to be an attainable perspective.…”
Section: Discussionmentioning
confidence: 99%
“…Possible mechanisms by which tolerance is induced by ITI include inhibition of B-cell memory and induction of T-cell anergy, anti-idiotypic antibodies, or suppressor T cells. 29 Overall, ITI is successful in ;70% of patients with hemophilia A and 30% of those with hemophilia B. 30 When successful, patients can return to using factor concentrates for the routine prevention and treatment of bleeding.…”
Section: Immune Tolerance Inductionmentioning
confidence: 99%